Juggling risk: lay perceptions of ecological and health risk in post-soviet mono-industrial Temirtau - Prilutskaya, Xeniya (Nazarbayev University School of Sciences and Humanities, 2016)
Temirtau is a mono-industrial post-Soviet city in Central Kazakhstan. Its large steel mill has caused serious environmental pollution for several decades already. This thesis focuses on how residents of Temirtau think about and deal with environmental and health risk. It considers how environmental discourse began to develop during the Soviet era and how it changed across the post-Soviet years, emphasizing the influence of political and cultural factors. Based on the analysis of the media discourses on environmental problems and industrial risks in Temirtau starting from the 1980s until the late 1990s, I argue that although Temirtau has not experienced natural or anthropogenic disaster such as those witnessed in Chernobyl or Fukushima, nevertheless Temirtau residents experienced a breakdown in public trust over the period from the late 1980s to the early 1990s. This breach of trust was connected with Perestroika and Glasnost.
Қатермен ойнау: посткеңестік моноиндустриялы Теміртаудағы экологиялық қауіп-қатер мен денсаулық зардабы туралы күнделікті түсінік
Жонглируя риском: бытовое восприятие экологического риска и риска для здоровья в постсоветском моноиндустриальном Темиртау
Keywords: risk; Temirtau; health risk; ecological risk; денсаулық зардабы; экологиялық қауіп-қатер; экологический риск; риск для здоровья; environmental problems; industrial risks in Temirtau; Central Kazakhstan; Темиртау; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas::Environmental medicine